PARP inhibitor cyanine dye conjugate with enhanced cytotoxic and antiproliferative activity in patient derived glioblastoma cell lines. Issue 14 (15th July 2020) - Choi, Peter J.; Cooper, Elizabeth; Schweder, Patrick; Mee, Edward; Turner, Clinton; Faull, Richard; Denny, William A.; Dragunow, Mike; Park, Thomas I.-H.; Jose, Jiney
Graphical abstract: Abstract: We describe the synthesis and in vitro activity of drug-dye conjugate 1, which is a combination of the PARP inhibitor rucaparib and heptamethine cyanine dye IR-786. The drug-dye conjugate 1 was evaluated in three different patient-derived glioblastoma cell lines and showed strong cytotoxic activity with nanomolar potency (EC50 : 128 nM), which was a 780 fold improvement over rucaparib itself. We also observe a synergistic effect of 1 with temozolomide (TMZ), the standard drug for treatment for glioblastoma even though these cell lines were resistant to TMZ treatment. We envisage such conjugates to be worth exploring for their utility in the treatment of various brain cancers.